Pemilihan Minat Bakat Oleh Siswa Sebagai Penunjang Revolusi Industri 4.0 : Untuk Masuk Ke Jenjang Perguruan Tinggi (Current Research in Education: Conference Series Journal, 2022)
Knowledge and technology are developing very rapidly and resulting in very fast and competitive changes in the era of the industrial revolution 4.0. In the 21st century, there is a problem where there are still many students who do not know what their interest and talents have, so it is difficult for them to choose a major, even some who choose majors at random and then cannot complete their studies or in other words drop out halfway because of the major taken only for the escape. In the 21st century, education in the world is undergoing various changes. By utilizing the era of the industrial revolution 4.0, the expected learning process is learning that forms and develops various kinds of students in an integrated manner, therefore the process of teaching and learning activities must realize efforts to form student character with the development of the student's personality, that way students will know the potential and interests of their talents